2015
DOI: 10.1002/fsn3.235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage on the chemical composition, microbiological load, and sensory properties of cassava starch‐based custard powder

Abstract: The effect of storage on the chemical, microbiological, and sensory properties of cassava starch-based custard powder (CbCP) blends as mixture of yellow-fleshed cassava root starch (YfCRS) (90–98%) and whole egg powder (WEP) (2–10%) was investigated. These were prepared using central composite rotatable design, and separately packaged in polyvinyl chloride plastic can and stored in storage box (30 ± 2°C). The chemical and microbiological analyses of the stored CbCP were evaluated at 3 weeks intervals, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The biofortified rice was preferred (73%) over control The biofortified rice variety should be introduced in Cuba because it can possibly help in the prevention of anemia and zinc deficiency Cassava Talsma et al (2013) 20 Kenya Consumers: Caretakers, 97% F, mean age: 32 y; n = 30 School children, 63% F, 6–12 y; n = 30 Preference test and blinded triangle discrimination test with boiled and mashed yellow and white cassava Caretakers and children were able to discriminate between yellow and white cassava; > 70% preferred yellow cassava. Characteristics of yellow cassava: attractive color, soft texture, sweet taste Yellow cassava is acceptable to schoolchildren and their caretakers Njoku et al (2014) 56 Nigeria Producers and consumers: Adults in the southeast, > 20 y; n = 30 Sensory attributes study (4-point hedonic scale) for color, taste, texture, mealiness, and appearance of eba made of gari from 3 yellow cassava varieties and 1 white cassava variety mixed with palm oil Yellow cassava was preferred over white because of the color, premium price, nutritional value, and texture Yellow cassava can be adopted by farmers if made available Awoyale et al (2015) 36 Nigeria Consumers: Trained panel, adults; n = 12 Sensory attributes study (9-point hedonic scale) for acceptability of mouth feel, taste, color, flavor, appearance, and of a gruel made of different mixtures of yellow cassava starch–based custard powder (90%–98%) with egg powder (2%–10%) measured at 0, 6, 12, 18, and 24 wk of storage Blend ratios and storage conditions affected the acceptance. At 24 wk, color and taste were disliked, which might be because of increase in moisture during storage Yellow cassava custard can be stored for 24 wk and still be acceptable Oparinde et al (2014) 55 Nigeria Consumers: Rural cassava consumers, 65% M > 18 y; n = 671 Sensory attributes study (5-point hedonic scale) for color, feel, taste, and drinking quality of gari and color and feeling for eba made from white, light yell...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biofortified rice was preferred (73%) over control The biofortified rice variety should be introduced in Cuba because it can possibly help in the prevention of anemia and zinc deficiency Cassava Talsma et al (2013) 20 Kenya Consumers: Caretakers, 97% F, mean age: 32 y; n = 30 School children, 63% F, 6–12 y; n = 30 Preference test and blinded triangle discrimination test with boiled and mashed yellow and white cassava Caretakers and children were able to discriminate between yellow and white cassava; > 70% preferred yellow cassava. Characteristics of yellow cassava: attractive color, soft texture, sweet taste Yellow cassava is acceptable to schoolchildren and their caretakers Njoku et al (2014) 56 Nigeria Producers and consumers: Adults in the southeast, > 20 y; n = 30 Sensory attributes study (4-point hedonic scale) for color, taste, texture, mealiness, and appearance of eba made of gari from 3 yellow cassava varieties and 1 white cassava variety mixed with palm oil Yellow cassava was preferred over white because of the color, premium price, nutritional value, and texture Yellow cassava can be adopted by farmers if made available Awoyale et al (2015) 36 Nigeria Consumers: Trained panel, adults; n = 12 Sensory attributes study (9-point hedonic scale) for acceptability of mouth feel, taste, color, flavor, appearance, and of a gruel made of different mixtures of yellow cassava starch–based custard powder (90%–98%) with egg powder (2%–10%) measured at 0, 6, 12, 18, and 24 wk of storage Blend ratios and storage conditions affected the acceptance. At 24 wk, color and taste were disliked, which might be because of increase in moisture during storage Yellow cassava custard can be stored for 24 wk and still be acceptable Oparinde et al (2014) 55 Nigeria Consumers: Rural cassava consumers, 65% M > 18 y; n = 671 Sensory attributes study (5-point hedonic scale) for color, feel, taste, and drinking quality of gari and color and feeling for eba made from white, light yell...…”
Section: Resultsmentioning
confidence: 99%
“… 55 Custard powder from yellow (provitamin A biofortified) cassava starch lost its acceptability after 24 weeks of storage, as evaluated by a Nigerian panel trained to recognize and differentiate food sensory properties (n = 12). 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level in the control sample was below the TFC reported by Simi et al [32] for starch powder. Also, the TFC of Turmeric sample was lower than that reported by Awoyale et al [25] but higher than the TFC reported by Simi et al [32]. The higher TFC of pawpaw treated sample could be as a result of ill handling of the raw material.…”
Section: Microbial Counts In the Custard Productsmentioning
confidence: 53%
“…6 CFU/g) prescribed by the international Microbiological standards for bacteria contaminants for food [24]. The result for the TBC was below the value (15.05×10 4 CFU/g) reported by Awoyale et al [25] for cassava starch based custard.…”
Section: Microbial Counts In the Custard Productsmentioning
confidence: 56%